Biosynthetic hydrogen isotopic fractionation factors during lipid synthesis in submerged aquatic macrophytes: Effect of groundwater discharge and salinity. (November 2017) - Aichner, Bernhard; Hilt, Sabine; Périllon, Cécile; Gillefalk, Mikael; Sachse, Dirk
Highlights: Hydrogen isotopic fractionation for Potamogeton grown in a lake and lab measured. δD values for plants collected from a lake unaffected by groundwater. δD values of plants grown in the lab became lower at higher salinity. Average ε value −136 ± 9‰ for freshwater samples. Abstract: Sedimentary lipid biomarkers have become widely used tools for reconstructing past climatic and ecological changes due to their ubiquitous occurrence in lake sediments. In particular, the hydrogen isotopic composition (expressed as δD values) of leaf wax lipids derived from terrestrial plants has been a focus of research during the last two decades and the understanding of competing environmental and plant physiological factors influencing the δD values has greatly improved. Comparatively less attention has been paid to lipid biomarkers derived from aquatic plants, although these compounds are abundant in many lacustrine sediments. We therefore conducted a field and laboratory experiment to study the effect of salinity and groundwater discharge on the isotopic composition of aquatic plant biomarkers. We analyzed samples of the common submerged plant species, Potamogeton pectinatus (sago pondweed), which has a wide geographic distribution and can tolerate high salinity. We tested the effect of groundwater discharge (characterized by more negative δD values relative to lake water) and salinity on the δD values of n -alkanes from P. pectinatus by comparing plants (i) collected from the oligotrophic freshwater Lake Stechlin (Germany) at shallow littoral depth from locations with and without groundwater discharge, and (ii) plants grown from tubers collected from the eutrophic Lake Müggelsee in nutrient solution at four salinity levels. Isotopically depleted groundwater did not have a significant influence on the δD values of n -alkanes in Lake Stechlin P. pectinatus and calculated isotopic fractionation factors εl/w between lake water and n -alkanes averaged −137 ± 9‰ ( n -C23 ), −136 ± 7‰ ( n -C25 ) and −131 ± 6‰ ( n -C27 ), respectively. Similar ε values were calculated for plants from Lake Müggelsee grown in freshwater nutrient solution (−134 ± 11‰ for n -C23 ), while greater fractionation was observed at increased salinity values of 10 (163 ± 12‰) and 15 (−172 ± 15‰). We therefore suggest an average ε value of −136 ± 9‰ between source water and the major n -alkanes in P. pectinatus grown under freshwater conditions. Our results demonstrate that isotopic fractionation can increase by 30–40‰ at salinity values 10 and 15. These results could be explained either by inhibited plant growth at higher salinity, or by metabolic adaptation to salt stress that remain to be elucidated. A potential salinity effect on δD values of aquatic lipids requires further examination, since this would impact on the interpretation of downcore isotopic data in paleohydrologic studies.